Halogenated ingredients of household and personal care products as emerging endocrine disruptors. (September 2022) - Klančič, Veronika; Gobec, Martina; Jakopin, Žiga
Abstract: The everyday use of household and personal care products (HPCPs) generates an enormous amount of chemicals, of which several groups warrant additional attention, including: ( i ) parabens, which are widely used as preservatives; ( ii ) bisphenols, which are used in the manufacture of plastics; ( iii ) UV filters, which are essential components of many cosmetic products; and ( iv ) alkylphenol ethoxylates, which are used extensively as non-ionic surfactants. These chemicals are released continuously into the environment, thus contaminating soil, water, plants and animals. Wastewater treatment and water disinfection procedures can convert these chemicals into halogenated transformation products, which end up in the environment and pose a potential threat to humans and wildlife. Indeed, while certain parent HPCP ingredients have been confirmed as endocrine disruptors, less is known about the endocrine activities of their halogenated derivatives. The aim of this review is first to examine the sources and occurrence of halogenated transformation products in the environment, and second to compare their endocrine-disrupting properties to those of their parent compounds (i.e., parabens, bisphenols, UV filters, alkylphenol ethoxylates). Albeit previous reports have focused individually on selected classes of such substances, none have considered the problem of their halogenated transformation products. This review therefore summarizes the available research on these halogenated compounds, highlights the potential exposure pathways, and underlines the existing knowledge gaps within their toxicological profiles. Graphical abstract: Image 1 Highlights: Halogenated transformation products are found in the environment and in human tissues. Halogenated derivatives disrupt different hormonal pathways than parent compounds. Halogenation in general decreases estrogen and androgen receptor activation. Introduction of halogens increases activation of thyroid and aryl hydrocarbon receptors.